2019
DOI: 10.3390/ijerph16183428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Specific Retinoic Acid Receptor Agonists on Noise-Induced Hearing Loss

Abstract: Noise is one of the most common causes of hearing loss in industrial countries. There are many studies about chemical agents to prevent noise-induced hearing loss (NIHL). However, there is no commercially available drug yet. Retinoic acid is an active metabolite of Vitamin A; it has an anti-apoptic role in NIHL. This study aims to verify the differences among selective agonists of retinoic acid receptors (RARs) in NIHL. All-trans retinoic acid (ATRA), AM80 (selective retinoic acid receptor α agonist), AC261066… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…18 Kwak et al veri ed the differences among selective agonists of retinoic acid receptors (RARs) in NIHL, in which selective agonists of RAR demonstrate comparable protective effects against NIHL to retinoic acid. 19 Although the direct association between Niacin and NIHL has not yet been studied, previous studies have reported the association between Niacin and age-related hearing loss (ARHL). In a rat model of stroke, niacin treatment signi cantly increased not only brain-derived neurotrophic factor (BDNF), but also synaptic plasticity and axonal growth.…”
Section: Discussionmentioning
confidence: 99%
“…18 Kwak et al veri ed the differences among selective agonists of retinoic acid receptors (RARs) in NIHL, in which selective agonists of RAR demonstrate comparable protective effects against NIHL to retinoic acid. 19 Although the direct association between Niacin and NIHL has not yet been studied, previous studies have reported the association between Niacin and age-related hearing loss (ARHL). In a rat model of stroke, niacin treatment signi cantly increased not only brain-derived neurotrophic factor (BDNF), but also synaptic plasticity and axonal growth.…”
Section: Discussionmentioning
confidence: 99%
“…3 School of Public Health, Nanjing Medical University, Nanjing, Jiangsu Province, China. 4 School of Public Health, Nantong University, Nantong, Jiangsu, China. Comparison of high-frequency hearing threshold shift of rs1053005 and rs1053023 genotypes in all subjects.…”
Section: Consent For Publicationmentioning
confidence: 99%
“…The authors declare that they have no competing interests. 4 , E-mail :zsh1994420@163.com; Baoli Zhu 1,2# ,E-mail:zhubaoli1965@126.com. 1 School of Public Health, Southeast University, Nanjing, Jiangsu Province, China.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…3 School of Public Health, Nanjing Medical University, Nanjing, Jiangsu Province, China. 4 School of Public Health,Nantong University, Nantong, Jiangsu, China. * These authors contributed equally to this article…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
See 1 more Smart Citation